Change in abdominal, but not femoral subcutaneous fat CT-radiodensity is associated with improved metabolic profile after bariatric surgery - Prince Dadson; Eleni Rebelos; Henri Honka; Luis E Juárez-Orozco; Kari K Kalliokoski; Patricia Iozzo; Jarmo Teuho; Paulina Salminen; Jussi Pihlajamäki; Jarna C Hannukainen; Pirjo Nuutila (ELSEVIER SCI LTD, 2022)
Background and aims: Computed tomography (CT)-derived adipose tissue radiodensity represents a potential noninvasive surrogate marker for lipid deposition and obesity-related metabolic disease risk. We studied the effects of bariatric surgery on CT-derived adipose radiodensities in abdominal and femoral areas and their relationships to circulating metabolites in morbidly obese patients. Methods and results: We examined 23 morbidly obese women who underwent CT imaging before and 6 months after bariatric surgery. Fifteen healthy non-obese women served as controls. Radiodensities of the abdominal subcutaneous (SAT) and visceral adipose tissue (VAT), and the femoral SAT, adipose tissue masses were measured in all participants. Circulating metabolites were measured by NMR. At baseline, radiodensities of abdominal fat depots were lower in the obese patients as compared to the controls. Surprisingly, radiodensity of femoral SAT was higher in the obese as compared to the controls. In the abdominal SAT depot, radiodensity strongly correlated with SAT mass (r =-0.72, p < 0.001). After surgery, the radiodensities of abdominal fat increased significantly (both p < 0.01), while femoral SAT radio density remained unchanged. Circulating ApoB/ApoA-I, leucine, valine, and GlycA decreased, while glycine levels significantly increased as compared to pre-surgical values (all p < 0.05). The increase in abdominal fat radiodensity correlated negatively with the decreased levels of ApoB/ApoA-I ratio, leucine and GlycA (all p < 0.05). The increase in abdominal SAT density was significantly correlated with the decrease in the fat depot mass (r =-0.66, p = 0.002).Conclusion: Higher lipid content in abdominal fat depots, and lower content in femoral subcutaneous fat, constitute prominent pathophysiological features in morbid obesity. Further studies are needed to clarify the role of non-abdominal subcutaneous fat in the pathogenesis of obesity. Clinical trial registration number: NCT01373892. (C) 2020 The Italian Diabetes Society, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition and the Department of Clinical Medicine and Surgery, Federico II University. Published by Elsevier B.V.